Measuring the efficiency of VAT reforms: a demand system simulation approach. (22nd December 2020) - Tóth, Peter; Cupák, Andrej; Rizov, Marian
Abstract: Using an estimated demand model, we simulate household-level demand responses to the recent Slovak value added tax (VAT) reform and its hypothetical alternatives. We use simulation results, instead of the standard approximate measures, for constructing an improved efficiency indicator of tax reforms as a ratio of welfare and fiscal revenue effects and call it marginal welfare gain (MWG). We also contribute to the literature on optimal structure of indirect taxes and on marginal tax reforms with new evidence of actual and hypothetical reforms that could increase the welfare of households at zero fiscal costs. Regarding the general policy implications of our results, we conclude that using a demand model to rank commodities according to their MWGs can be helpful for designing both efficient and equitable VAT reforms.